Lipidation Approaches Potentiate Adjuvant-Pulsed Immune Surveillance: A Design Rationale for Cancer Nanovaccine - Wang, Junqing; Zope, Harshal; Islam, Mohammad Ariful; Rice, Jamie; Dodman, Sage; Lipert, Kevin; Chen, Yunhan; Zetter, Bruce R.; Shi, Jinjun (Frontiers in Bioengineering and Biotechnology, 2020)
Adjuvant-pulsed peptide vaccines hold great promise for the prevention and treatment of different diseases including cancer. However, it has been difficult to maximize vaccine efficacy due to numerous obstacles including the unfavorable tolerability profile of adjuvants, instability of peptide antigens, limited cellular uptake, and fast diffusion from the injection site, as well as systemic adverse effects. Here we describe a robust lipidation approach for effective nanoparticle co-delivery of low-molecular weight immunomodulators (TLR7/8 agonists) and peptides (SIINFEKL) with a potent in vivo prophylactic effect. The lipidation ap-proaches (C16-R848 and C16-SIINFEKL) increased their hydrophobicity, that are intended to not only to improving drug encapsulation efficiency but also to facilitate the membrane association, intracellular trafficking and subcellular localization. The polymer–lipid hybrid nanoparticles (PLNs) are designed to sustain antigen/adjuvant levels with less systemic exposure. Our results demonstrated that a lipidated nanovaccine can induce effective immunity by enhancing the expansion and activation of antigen-specific CD8+ T cells. This adaptive immune response led to substantial tumor suppression with improved overall survival in a prophylactic setting. Our new methodology enhances the potential of nanovaccines for an-ti-tumor therapy.